Penyuluhan Perilaku Hidup Bersih dan Sehat (PHBS) Sebagai Upaya Pencegahan Terjadinya Demam Berdarah Dengue (DBD) dan Diare Pada Masyarakat di Desa Serigeni Lama - Ranida Arsi; Riski Amelia Putri; Dela Citra Nabela; Aria Duta; Sebrina Heleri Salim; Bella Alinggawati; Sittri Viora Audina; Donna Tipani; Triyanti Septa Sari; Putri Lestari; Annisa Bella Amanda; Lela Dewi Sartika (JURNAL PENGABDIAN KADER BANGSA, 2026)
Clean and Healthy Living Behavior (PHBS) is an important effort to improve public health and prevent various environmental-based diseases such as Dengue Hemorrhagic Fever (DHF) and diarrhea. Low public knowledge about PHBS can increase the risk of these diseases. Preliminary study results in Serigeni Lama Village showed that some community members had not fully implemented clean and healthy living behaviors in their daily lives. This study aimed to determine the implementation of PHBS counseling as an effort to prevent DHF and diarrhea in the community of Serigeni Lama Village. The research method used was descriptive with a quantitative approach using a one group pretest–posttest design. The activity was carried out on February 6, 2026, at the Serigeni Lama Village Hall with 95 community members participating in the counseling activity. The results showed that before the counseling, most participants were in the poor knowledge category with 45 people (47%), followed by moderate knowledge with 32 people (34%), and good knowledge with 18 people (19%). After the counseling, the good knowledge category increased to 67 people (71%), moderate knowledge became 21 people (22%), and poor knowledge decreased to 7 people (7%). In conclusion, PHBS counseling activities were effective in increasing community knowledge regarding the prevention of DHF and diarrhea through the implementation of clean and healthy living behaviors.